ANALISIS MANFAAT SISTEM INFORMASI UJIAN NASIONAL BERBASIS KOMPUTER DENGAN MENGGUNAKAN METODE DELONE DAN MCLINE - sudianto; Adha, Rizky (BRITech, Jurnal Ilmiah Ilmu Komputer, Sains dan Teknologi Terapan, 2019)
Computer-Based Test National Examination (UNBK) within the Ministry of Education and Culture using exam information system using a computer to obtain valid test results, and can be accountable. UNBK is a computer-based test or test that the presentation and selection is done computerized as a test medium. so that each test taker gets a different package of questions. The current UNBK operation uses a semi-online Virtual Hard Drive (VHD) system that is sent from an online central server via network (synchronization) to a local server, and then the execution of the student exams is served by the local server offline. The test results are then uploaded from the local server to the central server online. The local server uses the Virtual Machine application to run the UNBK server machine virtualization locally. Virtual machine application used is VirtualBox. The population of the study were all 10th grade students and 114 respondents. Data analysis using Structural Equation Modeling (SEM) with the help of IBM SPSS Amos v.20 software. The result of this research is user satisfaction variable has significant effect to intention to use and user satisfaction has significant effect to net benefit.